2021
DOI: 10.3390/mps4010017
|View full text |Cite|
|
Sign up to set email alerts
|

Concentration and Quantification of SARS-CoV-2 RNA in Wastewater Using Polyethylene Glycol-Based Concentration and qRT-PCR

Abstract: Wastewater-based epidemiology has become an important tool for the surveillance of SARS-CoV-2 outbreaks. However, the detection of viruses in sewage is challenging and to date there is no standard method available which has been validated for the sensitive detection of SARS-CoV-2. In this paper, we describe a simple concentration method based on polyethylene glycol (PEG) precipitation, followed by RNA extraction and a one-step quantitative reverse transcription PCR (qRT-PCR) for viral detection in wastewater. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 18 publications
1
47
0
1
Order By: Relevance
“…This knowledge was exploited for the design of novel in-house methods that combining random hexamers-based reverse transcription and nested PCR/real-time PCR amplification against four highly stable regions of SARS-CoV-2 RNA. The evaluation of our novel assays highlighted the improved LOD (up to two copies/PCR reaction) as compared with one-step RT-PCR methods [19,20], and the significantly improved sensitivity as compared with in-house CDC/2019-nCoV_N1-based assay. Interestingly, more than half of the positive samples were detected by using only one assay, highlighting the anticipated on-going degradation of SARS-CoV-2 RNA in wastewater and clearly demonstrates that SARS-CoV-2 RNA detection in wastewater is genomic region dependent.…”
Section: Discussionmentioning
confidence: 97%
“…This knowledge was exploited for the design of novel in-house methods that combining random hexamers-based reverse transcription and nested PCR/real-time PCR amplification against four highly stable regions of SARS-CoV-2 RNA. The evaluation of our novel assays highlighted the improved LOD (up to two copies/PCR reaction) as compared with one-step RT-PCR methods [19,20], and the significantly improved sensitivity as compared with in-house CDC/2019-nCoV_N1-based assay. Interestingly, more than half of the positive samples were detected by using only one assay, highlighting the anticipated on-going degradation of SARS-CoV-2 RNA in wastewater and clearly demonstrates that SARS-CoV-2 RNA detection in wastewater is genomic region dependent.…”
Section: Discussionmentioning
confidence: 97%
“…Peer-reviewed studies have compared PEG precipitation with other concentration methods for the recovery of a range of viruses and relevant surrogates (36)(37)(38)(39)(40). PEG precipitation (10%) has been preferred by a number of studies for providing the highest recovery of viruses and surrogates, and for its simple approach (i.e., low-cost equipment, accessible, no pre-treatment steps) (41)(42)(43)(44)(45)(46). Many of these recent findings are aligned with the results of this study, and Lu et al (2020) found that PEG methods were among the most common due to reliability, broad applicability, and accessibility (45) with that of non-enveloped MS2 by RT-qPCR and found that MS2 showed differences in recovery and was not a suitable indicator to validate the extraction and recovery of enveloped viruses (42).…”
Section: Discussionmentioning
confidence: 99%
“…On each sampling occasion, 500-1000 ml of crude influent was collected by manual grab sampling between 08.00 and 10.00 h, reflecting peak sewage flow and aiming to capture the highest community faecal load. Suspended solids were then removed from a 150 ml aliquot of each sample by centrifugation (3000 g, 4 °C, 30 min), and viral nucleic acids collected by subsequent PEG (polyethylene glycol 8000) precipitation for >18 hours based on methods described previously [34,35] with some minor modifications [36]. PEG precipitates collected by centrifugation (10,000g, 4 °C, 30 min), and pellets, resuspended in 200 μl of phosphate buffer saline, prior to RNA extraction in the Cardiff University COVID-19 Testing Service laboratory using automated BOMB protocol [33].…”
Section: Collection and Preparation Of Wastewater Samples For Varlock Assaysmentioning
confidence: 99%